Biochar-based ZrO2 doped adsorbents for removal of methyl orange dye from textile wastewater - Kurcin, Huriye Ceren; Aslan, Sevgi Kemec; Unlu, Derya (Inderscience Enterprises Ltd, 2025)
The industrial revolution has caused production and consumption rates to increase, which has consequently led to a rise in water usage. However, this case has also led to a rise in wastewater generation, posing a significant threat to the environment. Organic and inorganic substances present in wastewater mix with clean water sources, causing pollution in the environment. Particularly, compounds originating from industrial dyeing processes in textiles can be toxic to aquatic ecosystems. In this study, the removal of methyl orange in wastewater has been investigated by using ZrO2-modified grape and olive waste-derived bio-adsorbents. The properties of the bio-adsorbents were determined through FTIR, XRD, BET, and SEM analyses, while the removal of methyl orange was evaluated using UV spectrophotometry. The influence of adsorbent dosage and pH on dye removal was examined. The results indicate that olive-based bio-adsorbents are effective in removing up to 88% of dye from water.
Keywords: adsorption; biomass; methyl orange; wastewater treatment